Análises da nova matriz econômica (NME) brasileira sobre o setor informal (%PIB) e PIB per capita - Machado, Leonardo Rocha Pinheiro (2024)
We used the synthetic control method to carry out a case study of the impact of the New Economic Matrix (NME) on the Brazilian economy that was responsible for the 2014-2016 crisis. In this period, GDP per capita fell by 9%, while informal sector production (%GDP) increased by around 3 p.p. The main novelty of this paper is to study informality via synthetic control, because, to the best of our knowledge, such implementation was not carried out for Brazil, nor for any other country that has suffered similar intervention. We compared the results of the set of policies implemented with two counterfactuals: one that takes into account all the countries available in the databases and another that selects only countries similar to Brazil. The first one works as a robustness analysis. We show that, in the absence of policies implemented in Brazil, in 2012, GDP per capita would be US$ 3,000 higher, while informal production (%GDP) would be around 2.75 p.p. smaller than the observed. Furthermore, if Brazil had followed the behavior of its counterfactual, it would be 14 (13) positions above the ranking among the countries with the highest GDP per capita (lowest informal production). The results of this work are in line with the results found in Matos (2016), showing that the recent strong deterioration of the Brazilian economy is explained more by internal than external factors, due to the absence of a similar impact on the comparison units taken into account in the two sets of donor pools. Additional analyzes carried out in Firpo and Possebom (2018), which build confidence intervals for the synthetic control estimates, are carried out and confirm the results obtained in the methodology developed by Abadie et al. (2010).